Pros and cons of using systemic acitretin in the paediatric population - Sadowska, Magdalena; Narbutt, Joanna; Skibińska, Małgorzata; Lesiak, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Acitretin, a synthetic analogue of vitamin A is widely used in dermatology. It has an important role in the treatment of psoriasis and keratinization disorders. In adults its safety and efficacy has been proven in many studies, but there are some concerns regarding the use of acitretin in paediatric population, especially in high doses and as a long-term therapy. In this article we present the main indications of acitretin in children as well as the positive and negative aspects of acitretin treatment in this age population.